AR-based interactive GeoGebra learning media for optimizing transformation geometry learning in higher education - Buchori, Achmad; Putra, Fredi Ganda; Rahmawati, Noviana Dini (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to create and develop interactive AR (Augmented Reality) GeoGebra learning tools for teaching transformation geometry to support a blended learning system. This approach employs the ADDIE development model, which consists of five phases. The research subjects include 50 fifth-semester students. The research instruments comprise validated questionnaires for material and media experts, student responses, and pre-test and post-test instruments that are both valid and reliable. The results indicate a high level of validity (90%) and excellent practicality as assessed by experts and users, with an N-gain of 0.39 in the experimental class, which outperformed the control class with an N-gain of 0.02. The study concludes that teaching transformation geometry using interactive GeoGebra learning media is more effective. This research implies leveraging the potential of AR technology integration in mathematics education to create interactive and effective learning experiences.